A sick day for Amos McGee - Stead, Philip Christian (Roaring Brook, 2010)
"Amos McGee, a friendly zookeeper, always made time to visit his good friends: the elephant, the tortoise, the penguin, the rhinoceros, and the owl. But one day--'Ah-choo!'--he woke with the sniffles and the sneezes. Though he didn't make it into the zoo that day, he did receive some unexpected guests."--Dust jacket.